An umbilical lesion. (22nd February 2021) - Lavery, M. J.; Vasile, C.; Cathcart, C.; Bell, H.; Khirwadkar, N.; West, E.; Mullen, L.
Abstract : Click here for the corresponding questions to this CME article.